EVALUATION OF BENGKULU PROVINCE REGIONAL REGULATION NUMBER 02 OF 2018 CONCERNING THE IMPLEMENTATION OF PUBLIC ORDER, COMMUNITY PEACE, AND COMMUNITY PROTECTION (STUDY ON STREET VENDORS IN THE PANORAMA TRADITIONAL MARKET OF BENGKULU CITY) - Subhan Fitriansyah; Harmiati; Edi Darmawi (Yayasan Wayan Marwan Pulungan, 2023)
This study aims to evaluate the Regional Regulation of Bengkulu Province Number 02 Year 2018 regarding Public Order Management, Community Peace, and Community Protection, specifically in the context of street vendors in Panorama Traditional Market, Bengkulu City. The research was conducted using a qualitative approach and a case study method. Data were collected through observations, interviews, and documentation and then analyzed descriptively. The findings reveal that the socialization of the regulation has been implemented by the Regional Public Order Agency of Bengkulu Province, although not fully executed. Sanctions for violating the rules include warnings, written notices, cessation or dismantling of operations, and fines. The evaluation concludes that the Regional Regulation of Bengkulu Province Number 02 Year 2018 aligns with the principles of governance and does not conflict with legal perspectives. However, it is recommended that the Regional Public Order Agency of Bengkulu Province be more consistent and effective in enforcing the regulation. At the same time, the local government needs to enhance coordination with the agency. Furthermore, street vendors in Panorama Traditional Market, Bengkulu City, are expected to comply with the regulations by refraining from selling on the sidewalks.